Character Education Values in the Cimande Pencak Silat Martial Arts Extracurricular Program at the Al-Amien Prenduan Islamic Boarding School, Sumenep, Madura 2023 - Haidar Rifqi Ghassany; Meri Hidayati (Penerbit Hellow Pustaka, 2025)
Character education is a very important foundation of the nation and needs to be instilled from an early age in children, as implemented by the Al-Amien Prenduan Islamic Boarding School, Sumenep, Madura. This Islamic boarding school in Pragaan District provides opportunities for its students to develop their competencies. One of them is in the martial art of pencak silat and answering the research focus, researchers use a descriptive qualitative approach and use phenomenal types of research and use research methods, interviewing and documentation. From the researcher's methods of processing and analyzing data to obtain data or information. The subjects of this research were taken from 4 (four) people responsible for cimande silat pancakes, 3 (three) administrators and 2 (two) students as well as literature review of data related to books and journals for the validity of researchers using tranggulation with source tranggulation. The research results show that the implementation overview has three stages of implementation activities, namely: opening activities, core activities, closing activities. Character education values in Cimande martial arts 5 things: religion, tolerance, nationalism, mutual cooperation, integrity values. Meanwhile, the benefits of character education values in Cimande martial arts are: training patience, mental training, training concentration, training alertness, training sensitivity, training discipline, training control, increasing knowledge, and keeping the body healthy.